Buddhism for sheep (London : Ebury Press, 1996)
Sheep are seriously underestimated creatures when it comes to spirituality and religious feeling. For the first time, this book recognizes their huge potential and offers ovine students of Buddhism everywhere the opportunity to focus their skills and follow the path to enlightenment. From meditation and mindfulness to the essential concepts of Zen, all the fundamentals are set out here in a series of concise interpretations of Buddhist teaching. Wonderfully illustrated by well-known illustrator Chris Riddell, this is the perfect gift with a difference.
Keywords: Buddhism -- Caricatures and cartoons; Buddhism -- Humor